Primary Health Care: health profile in home care (Research, Society and Development, 2020)
Objective: to analyze in the scientific literature the health profile of users assisted in home care services in primary health care. Methods: The electronic databases used were BDENF, LILACS and SciELO, with searches in studies published from 2011 to 2019, in the months of April and May 2020. Searches were obtained by crossing, the following descriptors: home care and profile of health. Twenty articles were included, the analysis indicated that the available evidence reports to the sociodemographic and clinical profile of users in home care, using therapeutic devices. Results: most users were women, elderly, married, with low education and low family income; neurological diseases were found to be the predominant factor for admission to home care and stroke was the most frequent diagnosis. Conclusion: The evidence allows reflection to prepare professionals for interventions at home and regarding the use of therapeutic devices in home care.